Colour image processing system for transient liquid crystal heat transfer experiments - Wang, Z; Ireland, P; Jones, T; Davenport, R (Publ by ASME, 1994)
A colour image processing system for liquid crystal heat transfer experiment has been developed. The system is capable of digitizing and processing the complete liquid crystal surface colour (hue) change history in a transient test and, together with a calibration, can give the complete history of surface temperature over a full surface. Two methods for automatically processing the hue history to give heat transfer coefficient distributions are presented. Both methods raise the accuracy of the transient technique above other approaches by using the redundancy inherent in the multiple surface temperature measurements. The first regression approach applied to the determination of both h and Tgas is reported. The uncertainty in all measurements has been quantified and examples of applications of both techniques given.